Caracterização mineralógica dos minérios de magnesita do conjunto mineiro Pedra Preta-Jatobá-Pomba (Serra das Éguas, Brumado, BA) - Luis Rodrigues Armoa Garcia (2004)
At the Brumado plant, magnesite fragments ranging in size from 70,0mm down to 28,6mm, are burned in kilns, in a calcination and sinterization process known as single burning, to produce dead-burned magnesite (magnesian sinter). Some ores are quite suitable to this process while others are disintegrated down to a powder. This degradation of the ore is called decrepitation. The fines that are produced in this way decrease the permeability to the gases, slowing down the calcination and, consequently, the furnace production. The kiln operators acquired an empirical knowledge of the different available ores behavior during the burning so that they avoid the usage of those that can potentially cause any harm. However, the causes of the phenomenon are unknown. The mineralogical, physical and chemical characteristics of ore samples and products from burning tests that simulate the single burning process are studied with the help of several analytical techniques. The aim of this study was to find out characteristics that could possibly contribute to the understanding of the problem in such a way that the raw materials could have a more rational and conscious usage. The results obtained lead to the conclusion that the main responsible for the keeping of the ores mechanical integrity after burning is the initial sintering made easier by some elements that are present in the ores that have an acceptable behavior. These elements are Mn, Fe3+ and Ti. Also, the indented contact between the magnesite crystals is considered to have a positive effect in decreasing decrepitation. On the other way,the low content of Mn and the presence of Ca and Fe2+ and straight contacts are considered to favor decrepitation.